Emerging Contaminants in Water: Detection, Treatment, and Regulation - Pontius, Frederick W. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Contaminants of emerging concern in water are an ongoing challenge globally. This Special Issue is devoted solely to emerging contaminants in water. Research papers in this Special Issue address sampling and analysis, treatment effectiveness, and regulation to limit human exposure. Emerging contaminants addressed include pharmaceuticals and personal care products, glyphosate, microplastics and nanoplastics, venlafaxine, and benzodiazepine. Regulation of emerging contaminants in drinking water is reviewed focusing on PFOA and PFOS.